Foley catheterisation versus oral misoprostol for induction of labour in hypertensive women in India (INFORM): a multicentre, open-label, randomised controlled trial. Issue 10095 (12th August 2017) - Mundle, Shuchita; Bracken, Hillary; Khedikar, Vaishali; Mulik, Jayashree; Faragher, Brian; Easterling, Thomas; Leigh, Simon; Granby, Paul; Haycox, Alan; Turner, Mark A; Alfirevic, Zarko; Winikoff, Beverly; et al.
Summary: Background: Between 62 000 and 77 000 women die annually from pre-eclampsia and eclampsia. Prompt delivery, preferably by the vaginal route, is vital for good maternal and neonatal outcomes. Two low-cost interventions—low-dose oral misoprostol tablets and transcervical Foley catheterisation—are already used in low-resource settings. We aimed to compare the relative risks and benefits of these interventions. Methods: We undertook this multicentre, open-label, randomised controlled trial in two public hospitals in Nagpur, India. Women (aged ≥18 years) who were at 20 weeks' gestation or later with a live fetus and required delivery as a result of pre-eclampsia or hypertension were randomly assigned (1:1), via computer-generated block randomisation (block sizes of four, six, and eight) with concealment by use of opaque, sequentially numbered, sealed envelopes, to receive labour induction with either oral misoprostol 25 μg every 2 h (maximum of 12 doses) or a transcervical Foley catheter (silicone, size 18 F with 30 mL balloon). Randomisation was stratified by study centre. The catheter remained in place until active labour started, the catheter fell out, or 12 h had elapsed. If the catheter did not fall out within 12 h, induction continued with artificial membrane rupture and oxytocin, administered through a micro-drip gravity infusion set. Fetal monitoring was by intermittent auscultation. The primary outcome was vaginal birth within 24 h. Due to the nature of the interventions, masking of participants, study investigators, and care providers to group allocation was not possible. We analysed by intention to treat. This trial is registered withClinicalTrials.gov, numberNCT01801410 . Findings: Between Dec 20, 2013, and June 29, 2015, we randomly assigned 602 women to induction with misoprostol (n=302) or the Foley catheter (n=300; intention-to-treat population). Vaginal birth within 24 h was more common in women in the misoprostol group than in the Foley catheter group (172 [57·0%] vs 141 [47·0%] women; absolute risk difference 10·0%, 95% CI 2·0–17·9; p=0·0136). Rates of uterine hyperstimulation were low in both the misoprostol and Foley catheter groups (two [0·7%] vs one [0·3%] cases; absolute risk difference 0·3%, 95% CI −0·8 to 1·5; p=0·566) and neonatal deaths did not differ significantly between groups (six [2·0%] vs three [1·0%] neonatal deaths; 1·0, −1·04 to 2·97; p=0·322). 17 serious adverse events (3%) were reported during the study: one case of intrapartum convulsion and one case of disseminated intravascular coagulation (both in the Foley group); ten perinatal deaths, including two stillbirths (both in the Foley catheter group) and eight neonatal deaths (n=5 in the misoprostol group and n=3 in the Foley catheter group); and five of neonatal morbidity, comprising birth asphyxia (n=3), septicaemia (n=1), and neonatal convulsion (n=1). Interpretation: Oral misoprostol was more effective than transcervical Foley catheterisation for induction of labour in women with pre-eclampsia or hypertension. Future studies are required to assess whether oxytocin augmentation following misoprostol can be replaced by regular doses of oral misoprostol tablets. Funding: Medical Research Council, Department for International Development, and Wellcome Trust Joint Global Health Trials Scheme.